New and Formerly Unknown Ormyridae Species from the United Arab Emirates (Hymenoptera, Chalcidoidea) - Zerova, M.D.; Seryogina, L.Ja.; Van Harten, A. (Вестник зоологии, 2012)
Three new species (Ormyrus qurrayahi Zerova, sp. n., O. punctellus Zerova, sp. n. and O. novus Zerova, sp. n.) are described. Two first species belong to diffinis species group (female gaster without dorsal median keel). O. novus sp. n. belongs to orientalis species group (female gaster with dorsal median keel). In addition, two Palaearctic species of the genus Ormyrus are recorded from the United Arab Emirates for the first time. A key to Palaearctic Ormyrus species is provided.